Internet memes as internet signs: A semiotic view of digital culture - Cannizzaro, Sara (Sign Systems Studies, 2016)
This article argues for a clearer framework of internet-based “memes”. The science of memes, dubbed ‘memetics’, presumes that memes remain “copying units” following the popularisation of the concept in Richard Dawkins’ celebrated work, The Selfish Gene (1976). Yet Peircean semiotics and biosemiotics can challenge this doctrine of information transmission. While supporting a precise and discursive framework for internet memes, semiotic readings reconfigure contemporary formulations to the – now-established – conception of memes. Internet memes can and should be conceived, then, as habit-inducing sign systems incorporating processes involving asymmetrical variation. So, drawing on biosemiotics, Tartu-Moscow semiotics, and Peircean semiotic principles, and through a close reading of the celebrated 2011 Internet meme Rebecca Black’s Friday, this article proposes a working outline for the definition of internet memes and its applicability for the semiotic analysis of texts in new media communication.